KARAKTERISTIK LAGU YANG SESUAI UNTUK ANAK DITINJAU DARI SEGI AMBITUS - Wulandari, Rina (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Music vocal at education institute have many problems in considerable song study. ambitus is one of solutions where a teacher can plan song activities for kids better with this references; first, a teacher must have music manuscript in his lesson plan. It would be better in music notation. Second, a teachers must identify low and high tones from the song, and then compare it with children ambitus. It must not lower than "a" and not higher than "f".